Regulation of the proline regulatory axis and autophagy modulates stemness in TP73/p73 deficient cancer stem-like cells. Issue 5 (4th May 2019) - Sharif, Tanveer; Martell, Emma; Dai, Cathleen; Singh, Sheila K.; Gujar, Shashi
ABSTRACT: Cancer stem-like cells (CSLCs) reside as a small population within tumors, which mostly contain a larger population of differentiated cells. With their unique self-renewing abilities, CSLCs remain refractory to various therapeutic interventions, which otherwise kill differentiated cancer cells, and thus are a major culprit behind cancer treatment failures and cancer relapse. Recently, the process of macroautophagy/autophagy has emerged as a potential therapeutic target for eliminating CSLCs, as autophagic homeostasis has been discovered to play an important role in the growth of cancer and normal stem cells, and is required for the maintenance of the non-differentiated state of CSLCs. Our current work now shows that the so-called 'tumor suppressor' TP73/p73 plays an unconventional role in CSLC biology, and positively regulates the growth and stemness of CSLCs through the modulation of autophagy. Our data show that TP73/p73 deficiency, promotes autophagy in CSLCs by activating the autophagy machinery involving AMPK-TSC-MTOR signaling. Mechanistically, TP73/p73 deficiency-induced autophagy occurs as a result of reduced ATP levels resulting from the metabolic perturbations within the proline regulatory axis. Collectively, these findings unveil novel therapeutically-relevant implications for autophagy in the TP73/p73-dependent regulation of stemness within CSLCs.